2015
DOI: 10.1136/bmjquality.u207447.w2977
|View full text |Cite
|
Sign up to set email alerts
|

Safer Wards: reducing violence on older people's mental health wards

Abstract: Through the Safer Wards project we aimed to reduce the number of incidents of physical violence on older people's mental health wards. This was done using quality improvement methods and supported by the Trust's extensive programme of quality improvement, including training provided by the Institute for Healthcare Improvement. Violence can be an indicator of unmet needs in this patient population, with a negative effect on patient care and staff morale. Reducing harm to patients and staff is a strategic aim of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 7 publications
0
22
0
Order By: Relevance
“…This data was measured continuously over a period of two years from early 2014 onward with each incident plotted, following a drive to record each incident of violence and aggression whether physical or verbal on incident reporting, and is published separately. [1]…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This data was measured continuously over a period of two years from early 2014 onward with each incident plotted, following a drive to record each incident of violence and aggression whether physical or verbal on incident reporting, and is published separately. [1]…”
Section: Resultsmentioning
confidence: 99%
“…The ward was involved prior to this project in improvement work to reduce violence and aggression. [1]…”
Section: Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…A 36% reduction in number of incidents of violence led to a 49% reduction in costs associated with violence. 9 A similar economic analysis of a reduction in physical violence on acute adult mental health wards showed that there was a saving of £181,296 attributable to a 40% reduction in violence over six wards (Supplementary files 4 and 5). 10 Improving safety and staff experience at work is likely to lead to a reduction in staff absence from work, as the above two case examples have quantified.…”
Section: Cost Avoidancementioning
confidence: 97%